KONSELOR DALAM PENGUATAN NILAI DAN MORAL: STRATEGI MEMBENTUK GENERASI RELIGIUS - M. Nikman Naser (Institut Agama Islam Negeri Bengkulu, 2019)
Moral education is very important for learners to improve intelligence, emotional and spiritual. The value and moral learners to note because the education in school was very instrumental in supporting development of learners. Writing aims to provide information to teachers and counselors to instill the importance of moral values and the learners. Student often perform acts that violate the values and morals. Moral education aimed at guarding the learners do the wrong deeds in accordance with existing norms in society, the nation’s moral decline that Indonesia is very good with high numbers in the teens, freesex, rampant use of illegal drugs, there was a brawl between students. This strategy is done the existence, responsibility, and yet how belief and practice againts those values need to be strengthened. Environment and peers influence the religious moral values in life. Counselors in terms in give it a role in shaping how to think, behave, and act to participant.